Energydrinks in der Notfallmedizin - verleihen nicht nur Flügel - Knapp, Jürgen; Zylla, Maura Magdalena; Schaper, A.; Michalski, D.; Hartwig, S.; Bernhard, M. (Notfall & Rettungsmedizin, 2018)
In recent years, the consumption of energy drinks has massively increased. For this reason, we see more and more patients in our emergency medical services and emergency departments who have consumed energy drinks and suffer from sympathomimetic side effects of the caffeine which is a main ingredient of energy drinks, e. g., palpitations, tachycardia, restlessness/anxiety/nervousness, electrolyte imbalances. On the other hand, numerous case reports have been published on the association of partly excessive energy drink consumption and severe typical emergency medical disease patterns, one would not associate with energy drinks as a triggering agent: myocardial infarction, aortic dissection, severe cardiac arrhythmias, cardiac arrest, cerebral infarction and hemorrhage, seizures, and hepatitis. Therefore, inquiry about the amount of the present and chronic consumption of energy drinks during the medical history taking may provide important information about a possible intoxications. In patients who seek medical help due to symptoms such as chest pain or neurological deficits after excessive consumption of energy drinks, appropriate differential diagnoses should be considered. In this systematic review, incidence, typical symptoms, and different diagnostic approaches for patients presenting with suspected intoxications with energy drinks are presented and discussed.